PENGARUH SPORT MASSAGE TERHADAP RECOVERY ATLET PANJAT TEBING - Kumara, Fiqky Ravinda; Haetami, Mimi; Hidasari, Fitri Puspa (Universitas Tanjungpura, 2024)
The issue addressed in this research is the condition of rock climbing athletes in the speed discipline world record who have not fully recovered, especially muscle fatigue due to previous intense training sessions. This muscle fatigue condition impacts subsequent training sessions, resulting in athletes being less optimal in executing the program provided by the coach. The objective of this research is to determine the effect of sports massage on the recovery of rock climbing athletes in the speed discipline world record. The population of this study consists of 5 individuals. The sample in this research was selected using total sampling. The research method employed is an experimental method with the One Group Pretest and Posttest Design. The analysis results indicate a significant influence of sports massage in accelerating the recovery of rock climbing athletes. From the t-test, it can be observed that the calculated t-value (7.38) is greater than the tabulated t-value (2.776), with an increase in percentage by 35%. Therefore, it can be concluded that there is an influence of sports massage in expediting the recovery of rock climbing athletes.